Iris Hanika's Treffen Sich Zwei: Reception, Analysis and Interpretation - Nitz, Kerry Alistair (11692660) (2013)
Iris Hanika’s commercially and critically successful novel Treffen sich zwei makes use of several techniques in the characterisation of its protagonists. Many of its reviews focus on the author’s deliberate placement of links to a wider literary context. Their interest extends from questions of genre-mixing through to the identification of direct quotes from other authors’ works. The critical preoccupation with intertexts demonstrates their importance for the readers’ response to the novel. More specifically, certain reviews highlight the important role intertexts play in the characterisation of the protagonists. This study catalogues the intertexts, metaphors and parodies in Treffen sich zwei and, by means of quantitative analysis, identifies high-level patterns in the use of these techniques. In particular, patterns are identified between, on the one hand, the different narrative functions of the intertexts and, on the other hand, the different ways in which they are interwoven in the text. The data also shows that distinct patterns are associated with each of the two protagonists and that certain patterns change in the course of the novel in parallel with the changes in the relationship between them. This quantitative evidence is supported by a more detailed, qualitative approach, which examines how specific intertexts or metaphors are used for the purposes of characterisation. In addition, variations in voice are used to distinguish the two main protagonists in a manner consistent with the intertexts and metaphors. It is thanks to the combination of these techniques that the theme of meeting encapsulated in the title, Treffen sich zwei, is woven into the textual fabric of the novel.